Device for germicidal disinfection of drinking water by using ultraviolet radiation - Semenov, A.A.; Kozhushko, G.M.; Sakhno, T.V. (Ye.A.Buketov Karaganda State University Publishing house, 2016)
The results of the physical implementation of nonchemical methods of bactericidal water disinfection by UV irradiation are presented. The necessary calculations dose inactivation of bacteria, depending on the size of the camera exposure, the power of the radiation source and the irradiation time are carried out. On the basis of theoretical calculations and experimental data the device for bactericidal inactivation of drinking water has been proposed.
Ультракүлгін сəуле көмегімен ауыз суды бактерицидті залалсыздандыру құрылғысы
Устройство бактерицидного обеззараживания питьевой воды ультрафиолетовым излучением
Keywords: UV-method; ultraviolet disinfection of drinking water; a dose of bactericidal disinfection; ultraviolet irradiation